Psychometric properties of instruments measuring competencies of research support librarian and self-directed learning traits - A. Samah, Nazrinda; Mohd Tahir, Lokman; Talib, Rohaya; Wan Mamat, Wan Ali @ Wan Yusoff (Serials Publications, 2017)
Librarians who work professionally in libraries must make themselves visible in the processes surrounding academic research. These research support librarians need to equip themselves with relevant competencies to play their share in supporting learning, enhancing teaching, improving research, providing services as well as anticipating the needs of academic researchers. In order to investigate these competencies, it is imperative to scrutinise the self-directed learning among the librarians because many studies have agreed that self-directed learning has an influence on competencies. In this study, the researcher analysed the validity and reliability of Competencies of Research Support Librarian instrument and Self-Directed Learning Traits instrument. The bank of items was developed from the Core-Competencies for Twenty-First Century CARL Librarians Model and Knowles' Andragogy-Adult Learning Theory as well as from an exhaustive literaturere view. Experts from librarianship and test and measurement areas reviewed the instruments in order to establish face and content validity. Internal consistency and reliability were measured using Cronbach's alpha and Rasch model. Thirty research support librarians of a local comprehensive university and a research university scores were used. The reliability test resulted in an overall value of.94. The results of the study yielded how trustworthy and dependable the instruments are and the effectiveness of the instruments in investigating the influence of self-directed learning on the competencies of research support librarian. © Serials Publications.